Sustainability balanced scorecard architecture and environmental investment decision-making - Suaad Jassem; Zarina Zakaria; Anna Che Azmi (Foundations of Management, 2020)
This study is centered around a set of research questions that aim to explain how sustainability balanced scorecard architectures with sustainability parameters either embedded or treated as a separate perspective relate to environmental investment decision-making. The research also examines the mediating role of sustainability balanced scorecard knowledge and moderating role of strategic risk information. This article presents the results and answers to the research questions via conducting an experimental study approach using a two-factor factorial design. This is possibly the first study that determines, through an experimental procedure conducted with managers working in large manufacturing companies, whether any significant difference exists in environmental investment decision outcomes when decision-makers are presented with either an architecture where sustainability is embedded with the traditional four perspectives of balanced scorecards versus when it is presented as a separate fifth perspective. Furthermore, the development of an integrated model is possibly a significant contribution to the extant literature.
Keywords: M41; D81; 650; sustainability balanced scorecard; SBSC architecture; environmental investment decision; SBSC knowledge; strategic risk information